1995
DOI: 10.1113/jphysiol.1995.sp020949
|View full text |Cite
|
Sign up to set email alerts
|

GABA‐induced facilitation of the periodic bursting activity of oxytocin neurones in suckled rats.

Abstract: 1 GABAergic innervation of oxytocin neurones is particularly abundant during lactation, but little is known about its functional role. In this study, the role of GABAA receptors in the suckling-induced bursting activity of oxytocin neurones was investigated in lactating rats. GABAA agonists or antagonists were applied by pressure injection into the immediate neighbourhood of recorded neurones while simultaneous recordings were made from oxytocin neurones in the contralateral supraoptic nucleus. 2. GABA and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 25 publications
3
61
1
Order By: Relevance
“…It was recently shown that GABA facilitated the bursting activity of OT neurons during lactation while inhibiting background activity (Moos, 1995). Furthermore, GABA A antagonists interrupted bursting (Moos, 1995;Voisin et al, 1995). These results suggest that GABAergic inputs play an important role in the maintenance of the mechanisms underlying the milk-ejection reflex.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…It was recently shown that GABA facilitated the bursting activity of OT neurons during lactation while inhibiting background activity (Moos, 1995). Furthermore, GABA A antagonists interrupted bursting (Moos, 1995;Voisin et al, 1995). These results suggest that GABAergic inputs play an important role in the maintenance of the mechanisms underlying the milk-ejection reflex.…”
Section: Discussionmentioning
confidence: 63%
“…Alternatively, if OT neurons are sufficiently depolarized, inhibitory inputs that transiently hyperpolarize the neuron and deactivate the SOR may induce a burst of action potentials. It was recently shown that GABA facilitated the bursting activity of OT neurons during lactation while inhibiting background activity (Moos, 1995). Furthermore, GABA A antagonists interrupted bursting (Moos, 1995;Voisin et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies examining the role of GABA in influencing the activity of SON oxytocin neurons in the lactating rat show that occupancy of the GABA A receptor is critical for these neurons to exhibit the intermittent, synchronized bursts of electrical activity necessary for milk ejection (Voisin et al, 1994(Voisin et al, , 1995Moos, 1995). Although similar studies have not, as yet, been undertaken in pregnant or parturient animals, it is highly likely that a powerful GABAergic influence also exists on magnocellular oxytocin neurons at this time.…”
Section: Gaba a Receptor Changes With Respect To Magnocellular Neuronmentioning
confidence: 94%
“…We have determined the complement of GABA A receptor subunits expressed by these hypothalamic magnocellular neurons and shown that, regardless of whether they synthesize oxytocin or vasopressin, they all express mRNA and protein for the ␣ 1 , ␣ 2 , ␤ 2 , and ␥ 2 subunits . Because evidence suggests a critical role for GABA in regulating the activity of adult hypothalamic magnocellular neurons via the GABA A receptor (Moos, 1995;Voisin et al, 1995), we questioned in this study whether these magnocellular neurons may represent a neural population in which fluctuations in GABA A receptor subunit expression may occur within a physiological context in the adult rat brain. Animals and tissue preparation.…”
mentioning
confidence: 99%
“…Instead, tonically released OT from these cells may activate local Ca 2ϩ stores (Lambert et al, 1994;Ludwig et al, 2002) and produce a second molecule such as an endocannabinoid (eCB) Hirasawa et al, 2004;Ohno-Shosaku et al, 2005), which would then function as the retrograde transmitter. These effects on GABA release (Kombian et al, 2002;de Kock et al, 2004) may also be an important determinant of firing patterns in these cells (Moos, 1995). For example, in response to appropriate physiological stimulation, OT neurons fire in brief high-frequency discharges that terminate quickly, whereas VP neurons exhibit longer-lasting bursts of lower frequency (Poulain et al, 1977;Belin and Moos, 1986).…”
Section: Introductionmentioning
confidence: 99%